1976
DOI: 10.1136/jcp.29.5.403
|View full text |Cite
|
Sign up to set email alerts
|

Classification of smooth muscle autoantibodies detected by immunofluorescence.

Abstract: Three hundred and twelve sera containing antibodies to smooth muscle (SMA) wer analysed for the immunofluorescence patterns they produced in various tissues. A classification is described based on the three main appearances in rat kidney. Some sera, mainly of low titre, reacted only with vessel walls (SMA-V), some stained vessels and renal glomeruli (SMA-G) and high titre sera, mainly from patients with chronic active hepatitis stained vessels, glomeruli, and intracellular fibrils in renal tubules (SMA-T). Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
8

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(88 citation statements)
references
References 21 publications
5
75
0
8
Order By: Relevance
“…The SMA was considered positive when both the vessels and glomeruli were nonparametric tests were used: a) Cochran Q and McNemar tests 38,39 to study the disagreement of general AAA seroposifluorescent, according to the classification of Bottazzo et al 10 The presence of stress fibers (Fig 1A and 1B only by the best technique determined after statistical analy- …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMA was considered positive when both the vessels and glomeruli were nonparametric tests were used: a) Cochran Q and McNemar tests 38,39 to study the disagreement of general AAA seroposifluorescent, according to the classification of Bottazzo et al 10 The presence of stress fibers (Fig 1A and 1B only by the best technique determined after statistical analy- …”
Section: Methodsmentioning
confidence: 99%
“…In 1973, the association between SMA and AAA in AIH was established by Gabbiani et al 43 As SMA is a heterogeneous autoantibody nificant disagreement in 1:40 (P Å .0005) and 1:80 dilutions (P Å .03) between techniques B and D (neither (several tissular structures can be stained by SMA), Bottazzo et al 10 proposed a classification according to one with sodium citrate treatment), as well as between techniques C and E (both with sodium citrate treat-renal fluorescence: a) vascular-pattern SMA (vessels Abbreviations: Å, AAA reactivity is equally intense in lower and higher dilutions; úLD, AAA reactivity is more intense in lower dilution; úHD, AAA reactivity is more intense in higher dilution; NS, data not significant; k, weighted kappa test. k* The weighted kappa test evidenced significant concordance between all compared dilutions (P°.05).…”
Section: Techniques Techniquesmentioning
confidence: 99%
“…In the kidney, SMA can have three patterns: SMA-V (vessels), SMA-VG (vessels and glomeruli) and SMA-VGT (vessels, glomeruli and tubules). SMA-VG and AMA-VGT patterns are more specific of AIH, but SMA-V pattern is frequently found in viral hepatitis (19,20) . The specificity for antigens present in the microfilaments (F-actin), characterizing anti-actin antibody (AAA) is specific, but not pathognomonic, of AIH and is well correlated with the presence of SMA-VGT pattern in IIF (21) .…”
Section: Diagnosismentioning
confidence: 99%
“…SMA can also be detected, always by IFL, using fibroblasts or HEp-2 cells. The VGT pattern corresponds to the microfilament staining of isolated fibroblasts and represents a cable pattern across the cell [18] actin" though there is no molecular proof as yet that actin is indeed the only or indeed the main target of VGT SMA.…”
Section: Autoantibodies Detected By Ifl and Their Reactantsmentioning
confidence: 99%
“…The antibody was often found in association with ANA, which was already a known marker of AIH, and tended to fade with steroid induced remission. Bottazzo et al [18] reported that the SMA staining arterial vessels (V), glomerular mesangium (G) and fibers surrounding the kidney tubules (T), responsible for the VGT pattern, was confined to an ag gressive for m of hepatitis now known to be AIH-1. The antigenic moiety mainly but not exclusively responsible for SMA activity in what in the 1970s was called CAH was identified as filamentous (F) actin [19][20][21] .…”
Section: Smooth-muscle Autoantibody (Sma)mentioning
confidence: 99%